INVESTIGATE OPTICAL PROPERTIES OF PURE AND NI DOPED ZnO NANO PARTICLES - SAI GOWRI R; MOHAMED ROSHAN M; IRFANA AMRIN M (The Bioscan, 2025)
In this paper Pure and Ni doped Zinc oxide nano particles were synthesized by hydrothermal method using zinc acetate as a precursor and varying the dopant concentration (x =0.02,0.04,0.06) at 72 hours. The effects of dopant concentration, on the crystallite size, electrical property and absorption properties have been studied. The X-ray diffraction results confirm the formation of hexagonal wrusite structure and crystallite size decreases with increasing dopant concentration. Optical property and bandgap values were calculated for the prepared samples using UV- Visible spectrophotometer.